Using hierarchical location names for scalable routing and rendezvous in wireless sensor networks. (27th July 2006) - Bian, Fang; Li, Xin; Govindan, Ramesh; Shenker, Scott
Until practical ad-hoc localisation systems are developed, early deployments of wireless sensor networks will manually configure location information in network nodes in order to assign spatial context to sensor readings. In this paper, we argue that such deployments will use hierarchical location names (for example, a node in a habitat monitoring network might be said to be node number N in cluster C of region R), rather than positions in a two- or three-dimensional coordinate system. We show that these hierarchical location names can be used to design a scalable routing system called HLR. HLR provides a variety of primitives including unicast, scoped anycast and broadcast, as well as various forms of scalable rendezvous. These primitives can be used to implement most of the data-centric routing and storage schemes proposed in the literature; these schemes currently need precise position information and geographic routing in order to scale well. We evaluate HLR using simulations as well as an implementation on the Mica-2 motes.